Sistem Pengelolaan Data Koperasi Mitra Rakyat Wlingi Menggunakan Prototype - Arsa, Rafi Dani; Santi, Indyah Hartami; Chulkamdi, M Taofik (J-INTECH (Journal of Information and Technology), 2023)
Mitra Rakyat Wlingi Cooperative is still facing problems in managing customer data. The problem occurs because data management is split into two media, namely Microsoft Excel and books, which results in data duplication. Difficulties arise when searching for a list of customers who have made transactions or simply making monthly reports carried out by cooperative officers. This occurs due to unsynchronized data storage, which also affects the efficiency of service to customers. To overcome this problem, the author built an integrated system for cooperative officers in accordance with their roles in order to minimize data duplication and provide accurate information. The Research and Development (R&D) type research method uses the Systems Development Life Cycle (SDLC) which applies a development approach using a prototype model. The application was created using a website-based bootstrap framework. The application is tested using the black box method which focuses on evaluating and observing the input and output results of the application so that it suits user needs, so as to improve the quality of cooperative management and the image of service to customers.